2013
DOI: 10.1021/ma4020092
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Radical Polymerization of 3-Methylenecyclopentene with N-Substituted Maleimides To Yield Highly Alternating and Regiospecific Copolymers

Abstract: High-molecular-weight diene copolymers with a regiospecific repeating structure were produced in a high yield during the alternating radical copolymerization of N-substituted maleimides (RMIs) and 3-methylenecyclopentene (MCP) as the cyclic 1,3-diene monomer including a reactive exomethylene moiety. The eminent copolymerization reactivity of MCP was in contrast to the predominant occurrence of the Diels−Alder reaction of isoprene with the RMIs rather than copolymerization. The highly alternating structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…As shown in Table 1 , the copolymer yield changed depending on the structure of N ‐substituents in the order of PhMI > CHMI > BMI. This order was consistent with the previous results for the copolymerization with MCP . Copolymerization of MAn with DMPD and PD produced copolymers in higher yields (49–73%) compared with those for RMI copolymers (14–51%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Table 1 , the copolymer yield changed depending on the structure of N ‐substituents in the order of PhMI > CHMI > BMI. This order was consistent with the previous results for the copolymerization with MCP . Copolymerization of MAn with DMPD and PD produced copolymers in higher yields (49–73%) compared with those for RMI copolymers (14–51%).…”
Section: Resultssupporting
confidence: 92%
“…In this study, we carried out radical copolymerization of PhMI, N ‐cyclohexylmaleimide (CHMI), N ‐ n ‐butylmaleimide (BMI), and MAn in the combination with DMPD and 1,3‐pentadiene (PD) as diene monomers ( Figure ), and investigated the structures and the thermal stability of the obtained copolymers. CHMI and BMI provided high‐molecular‐weight copolymers with MCP in the previous study . It was already revealed that N ‐substituents in the repeating RMI unit of the copolymers importantly determined their glass transition temperatures ( T g ) .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Differing from the facile formation of alternating copolymers with olefins, MAn readily reacts with 1,3‐diene compounds to predominantly yield Diels‐Alder adducts, but not alternating copolymers. Recently, it was reported that 3‐methylenecyclopentene as the cyclic 1,3‐diene monomer including a reactive exomethylene moiety produced an alternating copolymer during radical copolymerization with an electron‐accepting N‐substituted maleimide in a high yield . This was because Diels‐Alder reaction was totally suppressed due to the fixed s‐trans conformation of the cyclic diene monomer.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, β‐myrcene undergoes homometathesis to yield the ring‐closed product (RCP), 3‐methylenecyclopent‐1‐ene ( 2 ), which is ready to react with methyl acrylate to yield the corresponding cross‐metathesis product, methyl 2‐(cyclopent‐2‐en‐1‐ylidene)acetate ( 3 ). Although its synthesis has already been suggested in a Horner–Wadsworth–Emmons reaction by Shibasaki et al., this compound has not been described so far.…”
Section: Methodsmentioning
confidence: 99%